Main Trends in the Development of Human Resources in Trade - Ignatova, Nikolinka (Research Papers, 2021)
The object of the study are commercial enterprises. The subject of the analysis is the human resources in trade. The indicators analyzed are: number of employees by levels of education, labor productivity, labor costs, staff costs, structure of labor costs of employers for employees, the costs of research and development in trade, the costs of qualification of personnel, the movement of labor in trade. The aim of the study is to reveal the trends in the development of human resources in trade and to outline their strengths and weaknesses. The time period of the study is from 2008 to 2018.
Keywords: Labor productivity; Trade